2005
DOI: 10.1086/497708
|View full text |Cite
|
Sign up to set email alerts
|

Severely Incapacitating Mutations in Patients with Extreme Short Stature Identify RNA-Processing Endoribonuclease RMRP as an Essential Cell Growth Regulator

Abstract: The growth of an individual is deeply influenced by the regulation of cell growth and division, both of which also contribute to a wide variety of pathological conditions, including cancer, diabetes, and inflammation. To identify a major regulator of human growth, we performed positional cloning in an autosomal recessive type of profound short stature, anauxetic dysplasia. Homozygosity mapping led to the identification of novel mutations in the RMRP gene, which was previously known to cause two milder types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
168
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(174 citation statements)
references
References 36 publications
(49 reference statements)
3
168
0
Order By: Relevance
“…63 In contrast, cells with the CHH founder RMRP mutation had significantly increased levels of cyclin B2 mRNA. 63 Cyclin B2 is known to contribute to chromosomal instability through alterations of the mitotic spindle checkpoint, 64 which suggests another possible explanation for the bone marrow dysfunction seen in CHH. Recent work by Maida et al has revealed a connection between RMRP and TERT.…”
Section: Cartilage Hair Hypoplasiamentioning
confidence: 96%
See 3 more Smart Citations
“…63 In contrast, cells with the CHH founder RMRP mutation had significantly increased levels of cyclin B2 mRNA. 63 Cyclin B2 is known to contribute to chromosomal instability through alterations of the mitotic spindle checkpoint, 64 which suggests another possible explanation for the bone marrow dysfunction seen in CHH. Recent work by Maida et al has revealed a connection between RMRP and TERT.…”
Section: Cartilage Hair Hypoplasiamentioning
confidence: 96%
“…63 Thiel et al showed that, in cells overexpressing the RMRP mutants seen in anauxetic dysplasia, there were decreased cyclin A2 levels. 63 In contrast, cells with the CHH founder RMRP mutation had significantly increased levels of cyclin B2 mRNA.…”
Section: Cartilage Hair Hypoplasiamentioning
confidence: 99%
See 2 more Smart Citations
“…To date, 73 RMRP mutations have been reported (Ridanpaa et al 2001(Ridanpaa et al , 2002Bonafe et al 2002Bonafe et al , 2005Nakashima et al 2003;Kuijpers et al 2003;Harada et al 2005;Hermanns et al 2005;Thiel et al 2005). The 70A>G mutation is the most prevalent; it comprises 92% of mutations seen in the Finnish population and is commonly seen in other populations (Ridanpaa et al 2002).…”
Section: Introductionmentioning
confidence: 99%